Local arginase inhibition and low-dose sodium nitroprusside administration do not modulate heat loss responses in young and older men during exercise - Meade, Robert; Fujii, Naoto; McGarr, Gregory; Alexander, Lacy; Boulay, Pierre; Sigal, Ronald; Kenny, Glen (Université d'Ottawa | University of Ottawa, 2019)
Age-related impairments in cutaneous vasodilation and sweating may result from increased arginase activity (which can attenuate endogenous NO production), and/or altered NO sensitivity of the thermoregulatory end-organs (i.e., cutaneous vasculature and sweat gland). We evaluated whether local arginase inhibition or low-dose sodium nitroprusside (SNP; NO donor) modulate cutaneous vascular conductance (CVC) and sweat rate (SR) in young (n=9, 23±3 years) and older (n=9, 66±6 years) men during an exercise-heat stress. We also assessed the influence of these treatments during whole-body passive heating in older men (n=7, 64±7 years). During two 30-min bouts of moderate-intensity cycling (Ex1 and Ex2) in the heat (35˚C), CVC and SR were measured at forearm skin sites perfused with: 1) lactated Ringer’s (Control); 2) 5mM Nω-hydroxy-nor-Arginine + 5mM S-(2-boronoethyl)-L-cysteine (Nor-NOHA+BEC, arginase-inhibited); or 3) 1µM SNP. The influence of these treatments on CVC and SR was also evaluated at passively-induced elevations in esophageal temperature (∆Tes) equal to those in Ex1 (0.6°C) and Ex2 (0.8°C). In both age-groups, CVC and SR were similar to Control at Nor-NOHA+BEC and SNP during exercise (all P≥0.10). During passive heating however, CVC was augmented compared to Control by Nor-NOHA+BEC at ∆Tes of 0.6°C (23±8%CVCmax; P=0.04) and 0.8°C (20±7%CVCmax; P=0.04). By contrast, no effect of SNP on CVC was seen (both P≥0.66) and SR was not influenced by any treatment during passive heating (P=0.89). Thus, neither arginase inhibition nor low-dose SNP modulate CVC or SR during moderate exercise in the heat, but arginase attenuates CVC in older men during whole-body passive heat stress.
Keywords: Aging; Nitric oxide; Heat stress; Skin blood flow; Passive heating